Detection of Xanthomonas oryzae pv oryzae from seeds and leaves of rice (Oryza sativa) using hrp gene based BIO-PCR marker - SINGH, DINESH; SINHA, SHWETA; SINGH, RAVINDER PAL (The Indian Journal of Agricultural Sciences, 2015)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae is a serious disease of rice. Detection of pathogen from infected plant parts and seeds is important to eliminate pathogen from disease cycle. For detection of X. oryzae pv. oryzae from natural infected leaves and stored seeds, a polymerase chain reaction technique using hrp gene (hypersensitive response and pathogenicity) sequence of X. oryzae pv. oryzae based primers DXoo_hrp1F (5’- GGACCCTCCGGTTCTGAG-3’) and DXoo_hrp1R (5’-CTGCAGGCATTGCTTAAAGA-3’) were used to amplify at 384 bp DNA fragment. The specificity of the primer was tested with X. oryzae pv. oryzae along with other Xanthomonas species such as X. campestris pv. campestris, X. axonopodis pv. punicae and Ralstonia solanacearum. It amplified only DNA fragment of X. oryzae pv. oryzae at 384 bp. The developed set of primer was highly sensitive and detected 2.6 × 102 cfu/ ml of bacteria. The X. oryzae pv. oryzae was detected from naturally infected leaves of rice collected from the bacterial ooze as DNA template through conventional – PCR. To detect X. oryzae pv. oryzae from seeds, the bacterial culture was artificially inoculated on rice cv. Pusa Basmati 1 plant at flowering time and the matured seeds were harvested and stored for 8 months under ambient conditions. The bacterium was detected from seeds after 8 months of storage even 2 seeds/ml, when DNA of bacterium was extracted by short cut methods adding 95% ethanol through BIO-PCR. This method is reliable, more sensitive than conventional–PCR and may detect X. oryzae pv oryzae within 2 days from the seeds and other planting materials.